Analisis Proksimat Snack Bar dengan Substitusi Tepung Pisang Kepok (Musa paradisiaca linn) - Nur Nida Afiifah; Mia Srimiati (Jurnal Ilmiah Kesehatan (JIKA), 2020)
Utilization of bananas that are processed into flour can be a substitute for flour and increase local food thereby reducing the use of wheat flour. Objective: This study aimed to analyze the effect of Kepok banana flour substitution to produce snacks with nutritional value and organoleptic properties. Methods: This study was experimental with 4 treatments namely flour: banana flour in a row, F0 (100%: 0%), F1 (50%: 50%), F2 (25%: 75%), F3 (0 %: 100%). Results: F1 formula was chosen from the organoleptic test results as the selected formula with a ratio of 50%: 50% followed by proximate tests, ash content, water content, fat, protein, and carbohydrates respectively 11,96%, 1,54%, 18,95%, 7,68%, and 58,05%. Conclusion: Based on statistic tests on chemical properties, there were no significant differences in water, fat, protein and carbohydrate content between the control formula and the selected formula, while there were significant differences in the ash content between the control formula and the selected formula.